Evaluation and modelling of integral capacitors produced by interdigitated comb electrodes - Ramajo, Leandro Alfredo (2008)
Integral capacitors (IC) of one or two-layer printed wiring board (PWB) circuits were produced using comb electrodes fixtures and dielectric composites as the inter-electrode material. ICs were fabricated at laboratory scale, using copper comb electrodes and BaTiO3-epoxy composite materials deposited on a glass-Epoxy FR4 board. They were experimentally tested in order to obtain their electrical response. Furthermore, ICs behaviour was modelled through 2-dimensional models applying finite element method (FEM). Results showed that by this laboratory technique it was possible to obtained integral capacitors with low dielectric losses. Moreover, acceptable agreement was found between numerical and experimental capacitance results for all the different analysed ICs. In conclusion, 2D FEM models are a suitable tool to predict electric response of IC devices.